The Evolution of Leadership and Decision Making: A Systematic Literature Review Using Bibliometric Analysis - Mulyoto; Ayda, Erni (MultiTech Publisher, 2023)
Leadership and decision-making in the VUCA era are crucial. Leadership effectiveness in organizing and quality decision-making is demanded so that organizations can survive uncertain conditions. The purpose of writing this article is to find out the development of leadership trends and decision-making models in the last two decades. The method used is a systematic literature review using bibliometric analysis. The conclusion obtained that leadership began to trend and attracted the attention of researchers in the period 2008-2013, which was associated with organizational culture and the development of human resource competencies. Research is massive in 2014-2018, which discusses transformational and adaptive leadership models. Meanwhile, in the last five years, the topic of leadership and decision-making has been dominated by the COVID-19 pandemic and equality.